Effect of preoperative oral antibiotics in combination with mechanical bowel preparation on inflammatory response and short‐term outcomes following left‐sided colonic and rectal resections. Issue 6 (16th October 2019) - Golder, A. M.; Steele, C. W.; Conn, D.; MacKay, G. J.; McMillan, D. C.; Horgan, P. G.; Roxburgh, C. S.; McSorley, S. T.
Abstract : Background: Preoperative oral antibiotics in addition to intravenous antibiotics and mechanical bowel preparation (MBP) may influence the gut microbiome and reduce both the postoperative systemic inflammatory response to surgery and postoperative infective complications following colorectal resection. This propensity score‐matched study compared outcomes of patients undergoing left‐sided colonic or rectal resection with or without a combination of oral antibiotics and MBP. Methods: The addition of oral antibiotics and MBP to prophylactic intravenous antibiotics in left‐sided colonic and rectal resections was introduced in 2015–2016 at a single institution. Propensity score matching was undertaken to compare the effects of oral antibiotics plus MBP versus neither oral antibiotics nor MBP on the postoperative systemic inflammatory response and short‐term outcomes in patients undergoing left‐sided colonic or rectal resection between 2013 and 2018. Results: Of 396 patients who had propensity score matching for host, anaesthetic and operative factors, 204 matched patients were identified. The addition of oral antibiotics and MBP was associated with a significantly reduced postoperative inflammatory response (reduced postoperative Glasgow Prognostic Score) on day 3 (odds ratio (OR) 0·66, 95 per cent c.i. 0·44 to 0·99; P  = 0·013) and day 4 (OR 0·46, 0·30 to 0·71; P  = 0·001). Significantly reduced overall complications (OR 0·31, 0·17 to 0·56; P  < 0·001), infective complications (OR 0·41, 0·22 to 0·77; P  = 0·011), surgical‐site infection (OR 0·37, 0·17 to 0·83; P  = 0·024) and postoperative length of hospital stay (median 7 days versus 8 days in patients who had intravenous antibiotics alone; P  = 0·050) were also observed. Conclusion: Preoperative oral antibiotics and MBP in addition to prophylactic intravenous antibiotics were associated with a reduction in the postoperative systemic inflammatory response and postoperative complications in patients undergoing resectional left‐sided colonic or rectal surgery. Abstract : This single‐centre propensity‐matched cohort study compared postoperative outcomes in patients undergoing left‐sided colonic or rectal resection with or without preoperative oral antibiotics and mechanical bowel preparation. In 204 matched patients, the addition of oral antibiotics and mechanical bowel preparation was associated with a significant reduction in postoperative systemic inflammatory response, overall complications, infective complications, surgical‐site infection and length of hospital stay. Evidence of benefit Abstract : Antecedentes: La administración preoperatoria de antibióticos por vía oral ( preoperative oral antibiotics, OAB), además de por vía intravenosa y de la preparación mecánica del colon ( mechanical bowel preparation, MBP) puede afectar al microbioma intestinal y disminuir tanto la respuesta postoperatoria sistémica inflamatoria a la cirugía, como las complicaciones infecciosas postoperatorias tras una resección colorrectal. Este estudio emparejado por puntaje de propensión comparó los resultados de pacientes sometidos a resección del colon izquierdo o resección rectal con y sin una combinación de OAB y MBP. Métodos: La adición de OAB y MBP a la administración profiláctica de antibióticos por vía intravenosa fue introducida en 2015‐2016 en un centro médico. Se llevó a cabo un estudio emparejado por puntaje de propensión para comparar los efectos de OAB con MBP versus la no administración de OAB ni el uso de MBP sobre la respuesta postoperatoria sistémica inflamatoria a la cirugía y los resultados a corto plazo en pacientes sometidos a resección del colon izquierdo o resección rectal desde el 2013 al 2018. Resultados: De los 396 pacientes incluidos en el emparejamiento por puntaje de propensión relativo a factores relacionados con el huésped, anestésicos y operatorios, se identificaron 204 pacientes emparejados. La adición de OAB y MBP se asoció con una disminución significativa de la respuesta inflamatoria postoperatoria (disminución postoperatoria de la puntuación pronóstica de Glasgow el día 3 (razón de oportunidades, odds ratio, OR 0, 66, i.c. del 95% 0, 44‐0, 99, P = 0, 013) y el día 4 (OR 0, 46, i.c. del 95% 0, 30‐0, 71, P = 0, 001). También se observaron reducciones significativas de las complicaciones globales (OR 0, 31, i.c. del 95% 0, 17‐0, 56, P < 0, 001), complicaciones infecciosas (OR 0, 41, i.c. del 95% 0, 17‐0, 83, P = 0, 011), infecciones del sitio quirúrgico (OR 0, 37, i.c. del 95% 0, 17‐0, 83, P = 0, 024) y duración de la estancia hospitalaria postoperatoria (mediana 8 versus 7 días, P = 0, 05). Conclusión: La adición preoperatoria de OAB y MBP a la administración profiláctica de antibióticos intravenosos se han asociado con una disminución de la respuesta inflamatoria sistémica postoperatoria y de las complicaciones postoperatorias en pacientes sometidos a resección del colon izquierdo o cirugía rectal.